Hearing in 44–45 year olds with m.1555A>G, a genetic mutation predisposing to aminoglycoside-induced deafness: a population based cohort study. Issue 1 (5th January 2012) - Rahman, Shamima; Ecob, Russell; Costello, Harry; Sweeney, Mary G; Duncan, Andrew J; Pearce, Kerra; Strachan, David; Forge, Andrew; Davis, Adrian; Bitner-Glindzicz, Maria
Abstract : Background: The mitochondrial DNA mutation m.1555A>G predisposes to permanent idiosyncratic aminoglycoside-induced deafness that is independent of dose. Research suggests that in some families, m.1555A>G may cause non-syndromic deafness, without aminoglycoside exposure, as well as reduced hearing thresholds with age (age-related hearing loss). Objectives: To determine whether adults with m.1555A>G have impaired hearing, a factor that would inform the cost–benefit argument for genetic testing prior to aminoglycoside administration. Design: Population-based cohort study. Setting: UK. Participants: Individuals from the British 1958 birth cohort. Measurements: Hearing thresholds at 1 and 4 kHz at age 44–45 years; m.1555A>G genotyping. Results: 19 of 7350 individuals successfully genotyped had the m.1555A>G mutation, giving a prevalence of 0.26% (95% CI 0.14% to 0.38%) or 1 in 385 (95% CI 1 in 714 to 1 in 263). There was no significant difference in hearing thresholds between those with and without the mutation. Single-nucleotide polymorphism analysis indicated that the mutation has arisen on a number of different mitochondrial haplogroups. Limitations: No data were collected on aminoglycoside exposure. For three subjects, hearing thresholds could not be predicted because information required for modelling was missing. Conclusions: In this cohort, hearing in those with m.1555A>G is not significantly different from the general population and appears to be preserved at least until 44–45 years of age. Unbiased ascertainment of mutation carriers provides no evidence that this mutation alone causes non-syndromic hearing impairment in the UK. The findings lend weight to arguments for genetic testing for this mutation prior to aminoglycoside administration, as hearing in susceptible individuals is expected to be preserved well into adult life. Since global use of aminoglycosides is likely to increase, development of a rapid test is a priority.